(3eaJGM GdadGMs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s ((3Ydj Hf CMeO Hf eMeO GdHMQGfjs)
(3ChdgG (B:s
(3eHJhQI GdChd hjHOC GdehLhO efgG Hbhdg(B: ...(3hCcKQ YdeGFfG bOS Gddg CQhGMge de jPcQhg hbO PcQg HYVge (B...(3Ke Ef cGf hVhDc ef EfGA jecf GdGZJQGa efg aVYg Ydi jejfc(B...s
(3BNQgG (B:s
...(3hceG bhdg YR SdWGfg ZGaQ GdPfH hbGHd GdJhH TOjO GdYbGH Pj GdWhd MjK hLO UaI GdGfJbGe hLYdgG eMahaI HfYhJ GdYah hGdEMSGf (B...(3hCf dG jDNQfG HShA CYeGdfG jhe GdOjf Efg CQMe GdQGMejf(B...s
(3CJe JCdjag aj UaQ (B1015(3g`, hHYOg QSGdI CNQi aj BOGH GdOGYj eNJUQI ef cJGH GdYOI(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B102s
(3gOjI GdYGQajf(B:(3L(B2(3,U(B273s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs